A. Rewrite the basic adition rule P(Y or Z) = P(Y) = P(Z) - P(Y and Z) using the information tha Y and Z are independent events.

B. Use the rewritten rule to find P(Z) if P(Y or Z) = 0.69 and P(Y)= 0.44
in Statistics Answers by

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

1 Answer

Best answer
When the events are independent P(Y and Z)=P(Y)P(Z), so

A) P(Y or Z)=P(Y)+P(Z)-P(Y and Z)=P(Y)+P(Z)-P(Y)P(Z). Note that the second equals sign should have been +.

B) 0.69=0.44+P(Z)(1-0.44)=0.44+0.56P(Z), P(Z)=0.25/0.56=0.47 approx.
by Top Rated User (645k points)

Related questions

1 answer
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
82,917 questions
87,575 answers
4,217 users